2003
DOI: 10.1203/01.pdr.0000078273.08316.26
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Adenosine A1-Receptor Blockade with 8-Cyclopentyl-1,3-Dipropylxanthine in Hypoxemic Newborn Rabbits

Abstract: The key role of intrarenal adenosine in mediating the hypoxemic acute renal insufficiency in newborn rabbits has been well demonstrated using the nonspecific adenosine antagonist theophylline. The present study was designed to define the role of adenosine A 1 receptors during systemic hypoxemia by using the specific A 1 -receptor antagonist 8-cyclopentyl-1,3-dipropylxanthine (DPCPX). Renal function parameters were assessed in 31 anesthetized and mechanically ventilated newborn rabbits. In normoxia, DPCPX infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…As we previously reported, acute normocapnic hypoxemia in newborn rabbits was associated with a significant increase in RVR and a concomitant decline in RBF, GFR, MAP and diuresis [3][4][5][6]25]. We formerly demonstrated that renal hypoperfusion has a vasomotor origin and that the underlying mechanisms involve the complex activation and interaction of vasoconstrictor and vasodilator factors acting on renal arterioles, including angiotensin II [5], adenosine [3,4], or NO [6].…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…As we previously reported, acute normocapnic hypoxemia in newborn rabbits was associated with a significant increase in RVR and a concomitant decline in RBF, GFR, MAP and diuresis [3][4][5][6]25]. We formerly demonstrated that renal hypoperfusion has a vasomotor origin and that the underlying mechanisms involve the complex activation and interaction of vasoconstrictor and vasodilator factors acting on renal arterioles, including angiotensin II [5], adenosine [3,4], or NO [6].…”
Section: Discussionmentioning
confidence: 79%
“…All the methods have been described previously [3,5]. Briefly, the rabbits were anesthetized by intraperitoneal injection of 25 mg/kg body weight (BW) of sodium pentobarbital and were artificially ventilated via tracheotomy with an oxygen-enriched gas mixture (respiratory rate 40 breaths/min, tidal volume adjusted for age and weight).…”
Section: Animal Experimentsmentioning
confidence: 99%
See 3 more Smart Citations